The Life Cycle Reliability Evaluation of Optical Cable - Cui Limin; Wu Yunna (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Along with the optical fiber communication technology is widely used in power system, optical cable fault which will lead to failure has become an important factor influencing power grid reliability, but the existing optical cable evaluation index is single, only statistical cable fault conditions operation index, can not fully reflect the actual reliability of cable. This paper tries to construct a whole life cycle based on optical cable statistical reliability evaluation index system, uses the entropy method to evaluate the reliability of the optical cable is more objective, true, to carry out cable reliability research has certain reference significance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2379